The effect of psychological realism in 19th century & early 20th century fiction: a close study on Henry James’s The Portrait of a Lady & James Joyce's A Portrait of the Artist as a Young Man - Nadvi, Rhyan Nafi (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2023.